Hell’s History: The USW’s Fight to Prevent Workplace Deaths and Injuries from the 1992 Westray Mine - Thompson, Mark (Relations industrielles / Industrial Relations, 2017)
Thiis article reviews the book, "Hell’s History: The USW’s Fight to Prevent Workplace Deaths and Injuries from the 1992 Westray Mine," by Tom Sandborn.